Review of Creosote Pollution Toxicity and Possibilities of Bioremediation (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Creosote oil is a complex mixture of hydrocarbon compounds obtained from high temperature distillation of coal tar. It is used for over 100 years as a fungicide, insecticide, miticide, and sporicide to protect wood and is applied by pressure methods to wood products, primary utility poles and railroad ties. This treated wood is intended for exterior or outdoor uses only. Its commercial uses include railroad ties 70%, utility poles 15-20%, and other miscellaneous commercial uses 10-15%. Composition of the creosote depends on the source and it has typically 85% polycyclic aromatic hydrocarbons (PAHs), 10% phenolic compounds, and 5% heterocyclic. Between 20 and 40% of the total weight of typical creosote can be attributed to the 16 PAHs defined as priority pollutants by the United States Environmental Protection Agency (EPA). The production of creosote in the European Union (EU) has been estimated to be approximately 60.000-100.000 t per year. The presence of the toxic PAHs and phenolic compounds make creosote treated wood harmful for the environment at the end of its service life and direct or indirect human exposure to creosote treated wood may cause carcinogenic affect to kidney, liver, bladder, eyes and skin. In this presentation we review creosote environmental pollution toxicity and possibilities of remediation.